Respostas
respondido por:
2
se formos comparar com uma equação de segundo grau temos
ax² + bx + c = 0
2x² + 5x + 3 = 0
a = 2
b = 5
c = 3
Δ = b² - 4ac
Δ = 25 - 24
Δ = 1
x = -5 +-√1/4
x´= -5+1/4
x' = -4/4 = -1
x´´= -5 -1/4
x´´ = -6/4 = -3/2
ax² + bx + c = 0
2x² + 5x + 3 = 0
a = 2
b = 5
c = 3
Δ = b² - 4ac
Δ = 25 - 24
Δ = 1
x = -5 +-√1/4
x´= -5+1/4
x' = -4/4 = -1
x´´= -5 -1/4
x´´ = -6/4 = -3/2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás